P1-S2.07 STI rates and risk factors among female sex workers attending STI testing sites in Germany, January–December 2010. (10th July 2011) - Nielsen, S; Haar, K; Sailer, A; Hamouda, O
Abstract : Background: Epidemiological studies on female sex workers (FSW) in Europe are limited. Since January 2010, selected German local health departments (LHD) offering STI testing services, have collected test results and behavioural data among FSW attendees. Using the data collected from January to December 2010, we asses STI positivity rates and identify risk factors for acquiring STIs among FSW tested at LHDs in Germany. Methods: 30 LHDs throughout Germany voluntary submit quarterly reports with the number of FSW tested and found positive for any of the following STIs—HIV, Chlamydia (CT), Gonorrhoea (GC), Syphilis, Trichomoniasis (Tvag) and bacterial vaginosis (BV). Physicians provide basic demographic data, medical history relating to STI and information on where the FSW meet clients. In a separate questionnaire FSW provide information on for example, number of clients per week, sexual practices and drug use. Data for the in total 123 variables is consolidated and validated at the Robert Koch Institute. Uni- and multi-variable logistic regressions were used to identify relevant risk factors for being infected with CT, GC, Syphilis and/or Tvag (STI positive) and OR with 95% CIs were calculated. Results: In 2010, 6675 FSW were seen and a total of 19 557 STI tests were performed. Physicians provided background data for 1142 (17%) of all FSW seen and of these 399 provided additional behavioural data. Median age was 30 (range—15–77 years), 72% were born outside Germany. Overall 7% of all tests were positive. The most common diagnoses were—BV (32.1% of 2770 tests), CT (6.8% of 3807), Tvag (3.3% of 2529) and GC (3.0% of 4223). 1.3% (of 3191) were positive for Syphilis and 0.2% (of 3037) HIV positive. Risk factors associated with a higher chance of testing STI positive included—poor knowledge of German language, OR=3.6 (2.5 to 5.0), meeting clients on the street, OR=3.5 (2.3 to 5.3) and increased number of clients per week. The risk of STI decreased with year of age, OR=0.95 (0.93 to 0.97), and was lower among FSW meeting clients on the internet, OR=0.5 (0.3 to 0.7) and FSW with health insurance, OR=0.4 (0.3 to 0.5) see Abstract P1-S2.07 Table 1 . Conclusions: STI positivity rates, especially for HIV and syphilis seem relatively low among the FSW attending STI testing sites in Germany in 2010. FSW are a heterogeneous group and public health efforts should target those most at risk such as the young, migrant, uninsured and street-based women who sell sex.